DECREASING OF PHENOL CONCENTRATION IN BALIKPAPAN SEA WATER POLLUTED BY USING ADSORPTION METHOD - Yulianto, Muhamad; Sitorus, Saibun; Gunawan, Rahmat (JURNAL ATOMIK, 2020)
Research on decreasing of phenol concentration in the Balikpapan seawater polluted by using the adsorption method, the purpose of this study was to determine the characteristics of activated carbon and adsorption percent to adsorb phenols with time and weight variations of the adsorbent. The results of the characteristics of activated carbon using SEM show that the carbon pores after activation are greater than before activation. In addition, phenol adsorption with time variations in seawater samples obtained optimal time at 30 minutes with 62% and the weight variation of the adsorbent obtained percentage of maximum adsorption at a weight of 12 grams is 51.11%.